Trichophorum Pers. (Cyperaceae) — новий рід для флори України - Данилик, І.М.; Мигаль, А.В.; Кіш, Р.Я. (Інститут ботаніки ім. М. Г. Холодного НАН України, 2007)
Сообщается о находке в гербарии Национального природоведческого музея Венгрии (BP, г. Будапешт) гербарного образца Trichophorum cespitosum (L.) Hartm. (Cyperaceae Juss.) с территории Закарпатья, являющегося новым родом и, соответственно, новым видом для флоры Украины. Приведены номенклатурная цитата, морфологические описания, а также сведения об ареале и экологических особенностях этих таксонов. Указываются наиболее вероятные места произрастания T. cespitosum на территории Украинских Карпат. The herbarium speciman Trichophorum cespitosum (L.) Hartm. (Cyperaceae Juss.) from the territory of Transcarpathians had been found in the herbarium (BP) of National Natural Museum of Hungary (Budapest), which has been new genus and new species for the flora of Ukraine. Nomenclature quotation, morphology descriptions, information about area and ecology peculiarities are covered for these taxa. Supposition about the most probable habitats of T. cespitosum on the territory of the Ukrainian Carpathians are indicated.